DIGITAL TRANSFORMATION OF SCHOOLS IN 3T REGIONS: EVALUATION OF THE SCHOOL MOVER PROGRAM WITH THE CIPP MODEL - Rory, Sandry; Setiawan, Rizky (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to evaluate the digitalization program at the driving school Junior High School in West Seram Regency using the CIPP (Context, Input, Process, Product) evaluation model. The evaluation focuses on: (1) the context aspect, which includes the suitability of the program to the school's needs, vision and mission, and the readiness of the school environment; (2) the input aspect related to human resource competency and the availability of information and communication technology (ICT) infrastructure; (3) the process aspect, which focuses on the implementation of the use of digital devices in learning activities by teachers and students; and (4) the product aspect, which concerns the effectiveness of the program in improving the quality of learning, teachers' technological competencies, learning outcomes, and students' 21st-century skills. This research is an evaluation study with a quantitative descriptive approach combined with a qualitative approach. The study population included all junior high schools implementing the driving school digitalization program in West Seram Regency. The results showed that the context and input aspects were in the very good category, with adequate basic infrastructure, ICT devices, and initial teacher competencies. In the process aspect, teacher and student achievements were also in the very good category (84%-91%), although challenges related to digital literacy were still found in several schools. In the product aspect, the dominant achievement was in the very good category (71%-98%). Junior High School 4 West Seram showed the highest results (teachers 98% and students 90%), while Junior High School 8 Taniwel achieved the lowest achievement (teachers 83% and students 71%). The differences in results between schools indicate the need for further mentoring, especially in schools with the lowest achievements. Overall, the digitalization program proved effective in increasing ICT utilization, encouraging learning innovation, and strengthening students' motivation and 21st-century skills. These findings confirm that the implementation of school digitalization has contributed positively to improving the quality of education in West Seram Regency, but equitable distribution of infrastructure and continuous improvement of digital competencies for teachers and students are needed.